2006
DOI: 10.1523/jneurosci.3115-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Target Neurons in the Nucleus Tractus Solitarius Drive Sodium Appetite

Abstract: Sodium appetite can be enhanced by the adrenal steroid aldosterone via an unknown brain mechanism. A novel group of neurons in the nucleus tractus solitarius expresses the enzyme 11-␤-hydroxysteroid dehydrogenase type 2, which makes them selectively responsive to aldosterone. Their activation parallels sodium appetite in different paradigms of salt loss even in the absence of aldosterone. These unique aldosterone target neurons may represent a previously unrecognized central convergence point at which hormonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
187
4
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(204 citation statements)
references
References 61 publications
7
187
4
4
Order By: Relevance
“…3A, the AP, NTS, and dorsal vagal nucleus of normal rats were virtually devoid of c-Fos-activated neurons, while in Fig. 3B, which shows a series of sections through the dorsal medulla from a rat that was sodium-deprived for 8 days, only the 11-␤-hydroxysteroid dehydrogenase type 2 (HSD2) neurons of the NTS were c-Fos-activated, which confirms earlier data (12). Under both conditions, no c-Fos-labeled neurons were found in the AP.…”
Section: Resultssupporting
confidence: 86%
“…3A, the AP, NTS, and dorsal vagal nucleus of normal rats were virtually devoid of c-Fos-activated neurons, while in Fig. 3B, which shows a series of sections through the dorsal medulla from a rat that was sodium-deprived for 8 days, only the 11-␤-hydroxysteroid dehydrogenase type 2 (HSD2) neurons of the NTS were c-Fos-activated, which confirms earlier data (12). Under both conditions, no c-Fos-labeled neurons were found in the AP.…”
Section: Resultssupporting
confidence: 86%
“…Using advanced molecular probes, it is possible to document the activation or suppression of specific subgroups of neurons within these CNS circuits, which among a select number of cell types are unique in their response to alterations in sodium intake, as opposed to the common characteristic of many cell types responding to changes in sodium concentration in the extracellular fluid. An example of such activation and de-activation of critical neural pathways by variations in sodium intake in laboratory animals is portrayed in Figure 1, which is drawn from a previous publication from one of our laboratories (15). Findings reported by a number of other laboratories provide extensive, plausible evidence of a primary role for CNS regulation of sodium appetite (14).…”
mentioning
confidence: 96%
“…Recently, the enzyme 11β-hydroxysteroid dehydrogenase type 2 (HSD2) and the mineralocorticoid receptors (MR) were identified in the NTS along with common neurotransmitters; such neurons are termed 'aldosterone-sensitive HSD2 neurons' (2 -5). Furthermore, a number of studies have shown that the aldosterone-sensitive HSD2 neurons in the NTS are involved in sodium appetite or in regulation of body fluid circulation as they are selectively activated by sodium deficiency (2,4).…”
mentioning
confidence: 99%
“…Recently, Geerling and Loewy demonstrated that HSD2 neurons are activated under dietary sodium deprivation, suggesting that the aldosterone-sensitive HSD2 neurons in the NTS are involved in sodium appetite (2,4). Based on these studies and our data showing that microinjection of the MR antagonist eplerenone into the NTS reversed baroreflex sensitivity, we focused on the role of aldosterone-sensitive neurons in the NTS in baroreflex sensitivity.…”
mentioning
confidence: 99%